Facilitating Security Using Third Party Auditing Based on Fragmentation - Sekar, K; Babu, G.V. Ramesh; Sake, Sasidhar (International Journal of Computer Sciences and Engineering, 2025)
In Cloud computing, which is a evolving technology, security requirement is very essentials when the services are provided by the third party venders.This paper concentrates on a well-connected association between secure cloud storage and network coding. To overcome the problem of old cryptography encoding and to provide cloud surroundings with a reliable third party. This can prevent the possibility of all information about getting hacked at one time and additionally provides access management and safe removal file. Homomorphic digital signature makes use of better technology to facilitate access to authorized users only. The proposed protocol is highly economical and provides a reasonable intrusion from an anonymous party. Hence, the overall outcome expected from these tasks is to provide information access to cloud environments. The proposed systems reduce the time required to secure the new systematic structure of the Cloud Storage Protocol and provide security in uploading and downloading files.